Longitudinal Aortic Root Dilatation in Collegiate American‐Style Football Athletes - Jason V. Tso; Casey G. Turner; Chang Liu; Ganesh Prabakaran; Mekensie Jackson; Angelo Galante; Carla R. Gilson; Craig Clark; B. Robinson Williams; Arshed A. Quyyumi; Aaron L. Baggish; Jonathan H. Kim (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Clinically relevant aortic dilatation (>40 mm) and increased cardiovascular risk are common among retired professional American‐style football athletes. Among younger athletes, the effect of American‐style football participation on aortic size is incompletely understood. We sought to determine changes in aortic root (AR) size and associated cardiovascular phenotypes across the collegiate career. Methods and Results This was a multicenter, longitudinal repeated‐measures observational cohort study of athletes across 3 years of elite collegiate American‐style football participation. A total of 247 athletes (119 [48%] Black, 126 [51%] White, 2 [1%] Latino; 91 [37%] linemen, 156 [63%] non‐linemen) were enrolled as freshmen and studied at pre‐ and postseason year 1, postseason year 2 (N=140 athletes), and postseason year 3 (N=82 athletes). AR size was measured with transthoracic echocardiography. AR diameter increased over the study period from 31.7 (95% CI, 31.4–32.0) to 33.5 mm (95% CI, 33.1–33.8; P<0.001). No athlete developed an AR ≥40 mm. Athletes also demonstrated increased weight (cumulative mean Δ, 5.0 [95% CI, 4.1–6.0] kg, P<0.001), systolic blood pressure (cumulative mean Δ, 10.6 [95% CI, 8.0–13.2] mm Hg, P<0.001), pulse wave velocity (cumulative mean Δ, 0.43 [95% CI, 0.31–0.56] m/s, P<0.001), and left ventricular mass index (cumulative mean Δ, 21.2 [95% CI, 19.2–23.3] g/m2, P<0.001), and decreased E′ velocity (cumulative mean Δ, −2.4 [95%CI, −2.9 to −1.9] cm/s, P<0.001). Adjusting for height, player position, systolic blood pressure, and diastolic blood pressure, higher weight (β=0.030, P=0.003), pulse wave velocity (β=0.215, P=0.02), and left ventricular mass index (β=0.032, P<0.001) and lower E′ (β=−0.082, P=0.001) were associated with increased AR diameter. Conclusions Over the collegiate American‐style football career, athletes demonstrate progressive AR dilatation associated with cardiac and vascular functional impairment. Future studies delineating aortic outcomes are necessary to determine whether AR dilation is indicative of maladaptive vascular remodeling in this population.